Orbital and Adnexal IgG4-related disease: An insight into the clinical profile and management outcomes - Prabrisha Banerjee; Md. Shahid Alam; Kirthi Koka; Bipasha Mukherjee; Subramanian Krishnakumar (Indian Journal of Ophthalmology, 2025)
Purpose: IgG4-related disease is a multisystem disorder involving the orbit and adnexa. The purpose of the present study is to report the varied clinical presentations of IgG4-related ophthalmic disease (IgG4 ROD) and their management outcomes. Methods: This was a retrospective study carried out between January 2013 and December 2020. All patients fulfilling the criteria for diagnosis after histopathological and hematological examinations were included in the study. Demographic data, ophthalmic and radiological findings, surgical details, and management outcomes were analyzed. Results: A total of 21 patients (25 eyes) were included in this study. Twelve were females (57.1%), and nine (42.9%) were males. Four patients (19%) had bilateral involvement. Extraocular muscles (EOMs) and orbital soft tissue were the most common sites involved (n = 13, 52% and n = 12, 48%, respectively). Lacrimal gland was involved in eight cases (n = 8, 32%). Eleven eyes (44%) had multiple periocular and adnexal site involvement. Serum IgG4 titer was found to be elevated in 14 cases (66.7%). All the cases were treated with the oral steroid. Adjuvant immunosuppressant was recommended in seven cases (33%). Recurrence was observed in seven cases (33.3%) at a mean interval of 21.1 ± 16.1 months, and it was found to be three times more common in patients with raised serum IgG4 levels and those with EOM involvement. Conclusion: IgG4 ROD is a rare orbital and adnexal disorder. It can be associated with raised serum Ig G4 levels and systemic evaluation is mandatory. Steroids remain the main stay of management with immunosuppressants being added in refractory cases.